Tower Dungeon. 1 - Nihei, Tsutomu, 1971- (Kodansha USA Publishing, 2025)
"An evil necromancer slays the king and carries off his daughter, secreting her in the legendary Dragon Tower. To save the princess, her steadfast Royal Guard assays the stronghold, but the way is blocked by powerful eldritch creature . . . So, to supplement their forces in the face of mounting casualties, they press ordinary folks from the surrounding villages into service - including Yuva, a sturdy young farmboy with a strong back but no experience in battle, and only a battered old helm and wooden shield to protect him." --